Rural Consumer Behavior and Strategic Marketing Innovations: An Exploratory Study in Eastern India - Bhattacharya, Saurabh; Roy, Subhadip (Indian Journal of Marketing, 2014)
Rural India, of late, has received much desired attention from the marketers given the fact that the urban markets have either become saturated or sales have leveled off. Furthermore, given the fact that more than 60% of the Indian population lives in rural areas, it became worthwhile to investigate rural consumer behavior. The study also explores whether innovative marketing activities of firms targeted towards the rural consumers are meeting the criterion of affordability, accessibility, availability, and awareness. The present study addresses these research questions with the help of an exploratory study conducted across four villages in the state of West Bengal, India. The major findings from the study indicate that: 1) media used for advertisements or awareness differed across occupational categories, 2) grocery purchase is mostly on credit in contradiction to what is generally believed, 3) consumers were, at most, willing to travel 12 km to purchase grocery items, 4) consumption level may not be low, but low disposable income leads to purchases in small amounts, and 5) innovative marketing activities undertaken by firms in rural areas, though they meet the accessibility and awareness factors, are affected by problems related to affordability and availability, which act as major hindrances for the rural consumers.